The Perceived Value Analysis of Difference Income Levels Indonesia Customer in Joint Venture Life Insurance - Shella Prasetyo (Prosiding Industrial Research Workshop and National Seminar, 2018)
This research was conducted to examine income levels differences on perceived value variable of joint venture life insurance customers that operating in Indonesia. The test was measured using SPSS program by processing data as much as 243 respondents by testing hypotheses processed using Independent T-test. The research found the dimensions of emotional response, reputation, monetary price, and behavioral price have differences perceptions of the average value of income levels above five million betters than below. The dimension of quality shows opposite result that both of income levels not differences. This research lead agents or people in charge of prospects and clients to maximize service by paying attention to how to influence customers to feel worth the money, appropriate business paid with a sense of pleasure to buy and the reputation of the company must be maintained can show the credibility of the company.